Comportamento em serviço da madeira jovem de Tectona grandis L.f com diferentes acabamentos para uso em ambiente externo - Blanco Flórez, Jeimy (2016)
In order to use outdoors young wood of teak Tectona grandis L.f teak coming from reforestation, the aimed this study was to understand and evaluate their behavior in service due to the time and kind of coating applied. The study was divided into two parts, the first, simulation testing in service on uncoated wood. The second, accelerated aging tests in cycles 24, 48, 84, 168 and 256 hours in the uncoated wood, with stain coating and wax colorless. The color change was evaluated in the coordinate system CIElab, surface roughness and near infrared spectroscopy (NIR). Analyses were aided by photographs and Scanning Electron Microscopy. The teak wood had low resistance in service floors for maximum strength, being able to light traffic. The finish with stain provided greater protection to the wood, lower roughness and has remained constant over the aging cycles. The finish with stain provided greater protection to the wood, lower roughness and has remained constant over the aging cycles. The total color change (ΔE) for the uncoated wood and wood with wax was classified as perceived; however, for wood stain the change was barely perceived. Regressions based on NIR spectra showed moderate correlations which allowed predicting the colorimetric properties of wood. The young teak wood uncoated was stable in relation to the variation of color and roughness as a function of time, and with application of stain performed better, with minor variations for all parameters, so it is considered suitable for use outdoors.